PERFORMANCE EVALUATION OF BACTERIAL CELLULOSE REINFORCED POLYETHYLENE COMPOSITES - L. Indrarti; R. Yudianti; A. Syampurwadi; M. Karina (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2012)
PERFORMANCE EVALUATION OF BACTERIAL CELLULOSE REINFORCED POLYETHYLENE COMPOSITES. This paper discusses the influence of bacterial cellulose reinforced polyethylene composites on the physical and mechanical properties. Composites consisting of polyethylene and bacterial cellulose were prepared by extrusion and compression process. The content of bacterial cellulose subjected to polyethylene was set from 0-50 (w/w)% with the addition of 2 % Polyethylene Maleic Anhydride (MAPE). The effect of bacterial cellulose content in the composites was evaluated. The tensile strength and elongation at break of composite declined with increasing of bacterial cellulose, but the Young’s modulus increased, demonstrating that composite becoming more rigid. At 23 oC 50 % RH, tensile strength, break strain and modulus of elasticity of polyethylene was 21.2 MPa, of 270 % and 763 MPa respectively. With the bacterial cellulose loading up to 50 %, tensile strength dropped to be half, break strain to be less than 0.5 %, but Young’s modulus increased more than 230 %. In addition, the composite became more hydrophilic and more amorphous loading with bacterial cellulose.